2008
DOI: 10.1111/j.1365-3113.2007.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relevance of the genital sclerites of Neuropterida (Insecta: Holometabola)

Abstract: Segment 9 of male Raphidioptera, comprising tergite, sternite, gonocoxites, gonostyli and gonapophyses, is a benchmark for homologies in the male and female terminalia of the three Neuropterida orders Raphidioptera, Megaloptera and Neuroptera. The segments relating to genitalia are 9, 10 and 11 in males and 7, 8 and 9 in females. Results from holomorphological and recent molecular cladistic analyses of Neuropterida agree in supporting the sister‐group relationships between: (1) the Raphidioptera and the clade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
258
3
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(300 citation statements)
references
References 25 publications
30
258
3
9
Order By: Relevance
“…In the last 10 years, different relationships among the Neuroptera families have been proposed based either on the cladistic analysis of some selected morphological characters (Aspöck et al 2001), molecular data (Aspöck et al 2003;Winterton 2003;Haring & Aspöck 2004), the genital sclerites (Aspöck & Aspöck 2008), or the morphology of the larva head (Beutel et al 2010). In particular, morphological studies suggested that Mantispidae would be placed in a clade together with Berothidae, Rhachiberothidae and Dilaridae (the dilarid clade).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 10 years, different relationships among the Neuroptera families have been proposed based either on the cladistic analysis of some selected morphological characters (Aspöck et al 2001), molecular data (Aspöck et al 2003;Winterton 2003;Haring & Aspöck 2004), the genital sclerites (Aspöck & Aspöck 2008), or the morphology of the larva head (Beutel et al 2010). In particular, morphological studies suggested that Mantispidae would be placed in a clade together with Berothidae, Rhachiberothidae and Dilaridae (the dilarid clade).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, morphological studies suggested that Mantispidae would be placed in a clade together with Berothidae, Rhachiberothidae and Dilaridae (the dilarid clade). Moreover, a sister-group relationship of Coniopterygidae + dilarid clade has been hypothesized (Aspöck et al 2001;Aspöck & Aspöck 2008;Zimmermann et al 2009;Beutel et al 2010). On the contrary, Hemerobiidae and Chrysopidae would have to be placed in a separate clade.…”
Section: Discussionmentioning
confidence: 99%
“…The genus is noteworthy for the large body size, elongate forewings, long filiform antennae, protrudent compound eyes, undulating margins to the forewings, disruptive pattern of coloration resembling leaf pinnae, distinctly thickened MP branches resembling a leaf rachis, complicated venation, and an appendage close to the caudal segment (Fig. 1B) that resembles the gonapophysis lateralis of Osmylidae, a relatively primitive feature among Neuroptera (10). Although moderate-to small-sized lacewings are dominant among extant Neuroptera, such large species are frequently found in the Middle Jurassic, notably species of the Aetheogrammatidae, Kalligrammatidae, and Grammolingiidae (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Abdomen with 10 segments and with an appendix close to caudal segment. The appendix resembles the gonapophysis lateralis of Osmylidae, which represents a primitive character of Neuroptera (10).…”
Section: Diagnosismentioning
confidence: 99%
“…Nevertheless, Garnaconis n. gen. has the hind wing base of Rs very close to that of M, which is a character present in Aleuropteryginae and in Flintoconis Sziráki, second brucheiserine genus, while Brucheiser Navás, has highly modified fore and hind wing venation delicate to interpret (Riek, 1975). The polarity of this character remains controversial because even the sister-group relationships of Coniopterygidae within the Neuroptera remain debatable: Aspöck, Plant, and Nemeschkal (2001) supported a 'Coniopterygidae + Sisyridae' clade, while Haring and Aspöck (2004) and Aspöck and Aspöck (2008) supported a 'Coniopterygidae + dilarid clade' (see summary in Aspöck & Aspöck, 2007); Winterton, Hardy, and Wiegmann (2010) found Coniopterygidae as sister group of all other Neuroptera; Beutel, Friedrich, and Aspöck (2010) considered that the position of this family remains uncertain; Zimmermann and others (2011) considered them as sister group to the clade (Mantispidae + (Dilaridae + (Rhachiberothidae + Berothidae))); while Aspöck, Haring, & Aspöck (2012) proposed them as sister group of the (Dilaridae + (Mantispidae + (Rhachiberothidae + Berothidae))). Note that this last hypothesis, as for the sisyrid or dilarid hypotheses, is congruent with a basal position of Rs as a plesiomorphy for the Coniopterygidae.…”
Section: Discussionmentioning
confidence: 99%